2002
DOI: 10.1139/o02-153
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biology and regulation of nucleoside and nucleobase transporter proteins in eukaryotes and prokaryotes

Abstract: The molecular cloning of cDNAs encoding nucleoside transporter proteins has greatly advanced understanding of how nucleoside permeants are translocated across cell membranes. The nucleoside transporter proteins identified thus far have been categorized into five distinct superfamilies. Two of these superfamilies, the equilibrative and concentrative nucleoside transporters, have human members and these will be examined in depth in this review. The human equilibrative nucleoside transporters translocate nucleosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 128 publications
1
81
0
2
Order By: Relevance
“…1C). hENT1 70 -YFP and hENT1 34 -YFP, showed no mitochondrial localization and instead showed diffuse localization in the cytoplasm similar to that observed for MDCK cells expressing the YFP vector alone (mock cells; data not shown). These data suggested that amino acid residues 71-74 of hENT1 contained the mitochondrial targeting signal of hENT1.…”
Section: Mitchondrial Localization Of Truncated and Mutated Hent1-yfpsupporting
confidence: 73%
“…1C). hENT1 70 -YFP and hENT1 34 -YFP, showed no mitochondrial localization and instead showed diffuse localization in the cytoplasm similar to that observed for MDCK cells expressing the YFP vector alone (mock cells; data not shown). These data suggested that amino acid residues 71-74 of hENT1 contained the mitochondrial targeting signal of hENT1.…”
Section: Mitchondrial Localization Of Truncated and Mutated Hent1-yfpsupporting
confidence: 73%
“…Important structural determinants for recognition of nucleosides by membrane transporters and clinically used nucleoside drugs and resulting resistance mechanisms are reviewed. The reader is referred to recently published review articles on the molecular structure and function of NT proteins and their role in drug resistance (Mackey et al, 1998a;Baldwin et al, 1999;Vickers et al, 2000;Cabrita et al, 2002;Clarke et al, 2002).…”
Section: Human Nucleoside Transportersmentioning
confidence: 99%
“…Under normal conditions, adenosine is mainly generated at the intracellular level from S-adenosylhomocysteine by Sadenosylhomocysteine hydrolase and transported across cell membranes via purine transporters [29]. Level of adenosine in extracellular environment is controlled by nucleoside or purine transporters [30,31]. These purine transporters are divided into two main categories [32]: (1) equilibrative purine or nucleoside transporters, transporting nucleosides in/out, depending on the concentration of adenosine and (2) concentrative purine or nucleoside transporters, facilitating intracellular influx of adenosine against the concentration gradient.…”
Section: Adenosine As a Sensor For Inflammationmentioning
confidence: 99%